Excessive Hepatic Arterial-portal Venous Shunting May Predict Failure of Microparticle Localization in Hepatocellular Carcinomas - Tan, Andrew Eik Hock; Kao, Yung Hsiang; Xie, Wanying (World Journal of Nuclear Medicine, 2013)
Locoregional treatment of hepatocellular carcinomas using yttrium-90 (Y-90) microspheres is an emerging modality, and involves the administration of such radioactive particles directly into the hepatic arterial vasculature. We present the case of a 58-year-old gentleman undergoing evaluation for Y-90 microsphere therapy for hepatocellular carcinoma, in which our findings suggest that significant hepatic arterial portal venous shunting detected during the angiogram maybe a predictor of poor localization of microspheres in the turmor, and that centers that utilize body surface area (BSA) approaches for dosimetry should take note of such findings.
Keywords: Hepatocellular carcinoma; Y-90 microsphere therapy; arteria-portal venous shunting